Asymptotic equivalence of the solutions of the linear stochastic ito equations in the Hilbert space - Krenevych, A. (Інститут математики НАН України, 2007)
We obtain the suffcient conditions of asymptotic equivalence in mean square and with probability one of linear ordinary and stochastic Ito equations in the Hilbert space.